Laporan Pelaksanaan Musyawarah Intern Umat Beragama Islam se-Kalimantan Selatan, tanggal 18-21 September 1989, Banjarmasin (Panitia Penyelenggara Musyawarah Intern Umat Beragama Islam se-Kalimantan Selatan, 1989)
Harmony of Muslim community and their participation in national development of Kalimantan Selatan Province; proceedings of a congress.